Faktor-faktor yang Berhubungan dengan Pemanfaatan Posyandu Lansia di Gampong Reuhat Tuha Kecamatan Sukamakmur Kabupaten Aceh Besar - Fitria Ningsih; Ibrahim Ibrahim; Alma Aletta (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Posyandu for the elderly aims to improve the quality of life for the elderly. All activities in the Posyandu service for the elderly are provided free of charge. However, the utilization rate of posyandu for the elderly is still low. In 2021, the percentage of elderly posyandu visits in Gampong Reuhat Tuha is 23%, which shows that it is still below the target of 50%. This study aims to determine the factors associated with the use of posyandu for the elderly in Gampong Reuhat Tuha, Sukamakmur District, Aceh Besar District. This type of quantitative analytic research with cross sectional design. The population in this study were all elderly people aged 60 years in Gampong Reuhat Tuha as many as 138 people. The research sample was 60 people. The sample was taken by proportional random sampling. The study was conducted from 05 to 16 July 2022. The data was collected by interview and observation. The analysis used is univariate and bivariate analysis with Chi-Square test. The results showed that 60% of posyandu utilization for the elderly were lacking, 56.7% lacked family support, 48.3% poor physical condition, 15% difficult posyandu access, 36.7% negative perceptions, 48.3% stated the role of cadres was lacking and 63, 3% less knowledgeable. From the results of statistical tests it can be concluded that there is a relationship between family support (p = 0.001), physical condition (p = 0.007), perception (p = 0.004), the role of cadres (p = 0.031) and knowledge (p = 0.0001) with the use of Posyandu for the elderly in Gampong Reuhat Tuha, Sukamakmur District, Aceh Besar District. It is hoped that the Sukamakmur District Health Center in Aceh Besar can increase the participation of the elderly in the implementation of the posyandu for the elderly by increasing the support of the elderly family through health counseling and increasing the role of posyandu cadres.